Transpersonal practices as prevention intervention for burnout amongst HIV/AIDS coordinator teachers - Johnson, Sharon Mary (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Psychology))--University of Stellenbosch, 2010.